Semiochemical modulation of host preference of Callosobruchus maculatus on legume seeds. (July 2015) - Ajayi, Olufunmilayo E.; Balusu, Rahmmohan; Morawo, Tolulope O.; Zebelo, Simon; Fadamiro, Henry
Abstract: Host preference of Callosobruchus maculatus (F.) on seeds of three legume cultivars, Ife-brown and black-eyed cowpeas [ Vigna unguiculata L. (Walp)], and soybean ( Glycine max L.), was investigated. Mated female C. maculatus showed high (90–95%) attraction to the three legume cultivars in Y-tube bioassays. However, the weevils discriminated among the cultivars in four-choice tests and showed greater attraction to Ife-brown cowpea (50%) than to soybean (30%) and black-eyed cowpea (15%). Coupled gas chromatography-electroantennography (GC-EAD) and GC–MS analyses of the headspace volatile organic compounds (VOCs) emitted by the legume seeds identified 2-ethyl hexanol as the principal EAD active component. Emission of 2-ethyl hexanol was two-fold greater in Ife-brown cowpea (∼0.54 μg g −1 seeds) compared with black-eyed cowpea (∼0.23 μg g −1 seeds) and soybean (∼0.21 μg g −1 seeds). Synthetic 2-ethyl hexanol attracted 68% of female C. maculatus at 0.01 μg dose in Y-tube bioassays. These results demonstrated that host preference in C. maculatus is odor-mediated, and identified 2-ethyl hexanol as a potential attractant for C. maculatus . Graphical abstract: Highlights: We studied response of Callosobruchus maculatus to odors of three legume seeds. GC-EAD and GC-MS revealed 2-ethylhexanol as the bioactive component. Pure 2-ethylhexanol attracted the weevils at 0.01 µg dose. Host preference in C. maculatus is odor-mediated. 2-ethyl hexanol is a potential attractant for C. maculatus .